A green colorimetric approach towards detection of arsenic (III): A pervasive environmental pollutant. (April 2019) - Boruah, Bijoy Sankar; Biswas, Rajib; Deb, Pritam
Highlights: Here we have reported a colorimetric technique for detection of arsenic. Glucose, which is a biocompatible polymer is used for functionalized the gold nanoparticles. Addition of metal ions solutions to these functional nanoparticles solutions, only arsenic shows prominent color change. Limit of detection of this sensing unit is found to be 0.53 ppb. Abstract: The invasion of arsenic is slowly rising in aqueous medium which necessitates a rapid and cost effective detection. In quest to explore an effective way of monitoring arsenic (III) in aqueous medium, we report here a colorimetric method with novel green receptor viz. glucose in gold nanoparticles platform. With an average size of ∼44 nm and plasmon peak at ∼520 nm, these glucose functionalized gold nanoparticles show excellent selectivity towards arsenic (III) with a rapid color change from red to bluish. The detection unit is found to possess linearity in the range of 1–14 ppb with a remarkable limit of detection of 0.53 ppb which is well below the WHO guided value.